Boosting potato supply and demand in Southeast Asia. Project profile - International Potato Center (International Potato Center, 2019)
Potato has unexploited potential to contribute to the food security, nutrition, and livelihoods of resource-poor farmers in Southeast Asia. This project aims to identify suitable varieties that are early-maturing, high-yielding, disease-resistant and have good eating and processing characteristics, thereby boosting the supply of and demand for potato in the region.